Environmental Microbiology: Microbes and Their Roles in Ecosystems - Kasmawati; Nasution, Eni Sumanti (PT Inovasi Pratama Internasional, 2024)
Environmental microbiology is a critical field that explores the intricate relationships between microorganisms and their environments. This study investigates the roles of microorganisms in various environmental contexts, focusing on their diversity, abundance, and ecological functions. Samples were collected from agricultural soils, freshwater bodies, industrial wastewater, and urban air, and analyzed using culture-based and molecular techniques. The results revealed significant variations in microbial abundance and diversity across the sampled environments. Agricultural soils exhibited the highest microbial abundance and diversity, with nitrogen-fixing bacteria playing a crucial role in nutrient cycling. In contrast, freshwater bodies showed moderate diversity, while industrial wastewater had the highest abundance but lower diversity, with a high prevalence of hydrocarbon-degrading microorganisms. Urban air samples had the lowest abundance but relatively high diversity. The biochemical capabilities of the isolates further emphasized the ecological roles of these microorganisms, particularly in bioremediation and soil fertility. The findings underscore the importance of preserving microbial diversity for maintaining ecosystem health and resilience. This research highlights the need for integrating microbiological insights into environmental management policies and suggests future research directions to explore microbial interactions and their potential applications in biotechnology and environmental remediation.